2018
DOI: 10.1016/j.jhazmat.2018.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl acetate processing wastewater treatment using combined Fenton’s reagent and fungal consortium: Application of central composite design for conditions optimization

Abstract: The Fenton reaction as an oxidative degradation process was used for industrial chemical wastewater (ICW) pretreatment. The biodegradation of pretreated ICW was performed, in aqueous environment under aerobic condition, by a defined fungal consortium. The central composite design (CCD) was used to study the effect of nitrogen and phosphorus addition and the concentration of the pollution on the removal of polyvinyl alcohol (PVA) and organic compounds. The interaction between parameters was modeled using the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The underlying principle of selecting CCD-based experiments is based on its practicality for determining the optimal operating conditions . The CCD framework provides us with sets of experiments that probe the HTC operation with respect to three key process parameters that can affect the structural and morphological properties of hydrochars, namely (i) carbonization temperature80–250 °C, (ii) reaction time4–24 h, and (iii) microalgae/biomass weight ratio0:1 . The selected range for key process parameters was carefully chosen based on reports presented in previous literature. ,, Process optimization was carried out in design expert (version 10.0.4.0) and company Stat-Ease, Inc. 2016, generating 20 sets of test parameters that were experimentally executed and evaluated sequentially (Table S1, Supporting Information).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The underlying principle of selecting CCD-based experiments is based on its practicality for determining the optimal operating conditions . The CCD framework provides us with sets of experiments that probe the HTC operation with respect to three key process parameters that can affect the structural and morphological properties of hydrochars, namely (i) carbonization temperature80–250 °C, (ii) reaction time4–24 h, and (iii) microalgae/biomass weight ratio0:1 . The selected range for key process parameters was carefully chosen based on reports presented in previous literature. ,, Process optimization was carried out in design expert (version 10.0.4.0) and company Stat-Ease, Inc. 2016, generating 20 sets of test parameters that were experimentally executed and evaluated sequentially (Table S1, Supporting Information).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…From 1 H‐NMR results it can be seen that there was no obvious difference peak found. That is, after oxidation chain scission of sodium hypochlorite, the product is indeed PVA 32 . The three peaks at 4.3 to 4.8 ppm from left to right correspond to the isotactic, syndiotactic, and random structures of the hydroxyl group [OH] of polyvinyl alcohol 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Dilution reduces the amount of pollutants present in the effluent and improves the growth and metabolism of fungal species; moreover, it increases the COD removal and decolorization efficiency of the effluent (Deepika and Dastidar, 2016;Strong, 2010). Therefore, COD removal and decolorization dilution was the most effective parameter (Ajmi et al, 2018). The results showed that by enhancing the dilution rate from 90% to 25%, the removal efficiency of COD removal and decolorization also enhanced, which could be owing to the lower contaminant concentration at dilution of 25%; therefore, the fungi had a higher potential to remove effluent pollutants (Figures 4 and 5).…”
Section: Effect Of Dilution On Chemical Oxygen Demand Removal and Decolorization Efficiency By Mixed Fungal Culturementioning
confidence: 99%
“…The results of this research confirm the ability of predominant native fungi for COD removal and decolorization from cardboard recycling industrial effluent. As decolorization and COD removal of the effluent are natural, bioremediation of the wastewater by mixed fungal culture may be owing to the use of these pollutants as a carbon source and the energy source for enzyme growth and production (Ajmi et al, 2018;Tyagi et al, 2014).…”
Section: Effect Of Dilution On Chemical Oxygen Demand Removal and Decolorization Efficiency By Mixed Fungal Culturementioning
confidence: 99%